KEPUASAN PERAWAT SETELAH MELAKUKAN OVERAN SISI PASIEN DENGAN KOMUNIKASI SBAR - Manurung, Idawati; Udani, Giri (Jurnal Kesehatan, 2019)
Hospital service quality must be improved, one aspect is patient safety, its efforts are through increased effective communication. One of the indicators is communicates using the SBAR method. The handover between shift at the hospital has not carried out handover at the patient's side by using the SBAR method and has not been oriented to the patient's condition. Therefore nurses have not focused on the development of the condition of the patients and did not provide nurse satisfaction their nursing care performed. The study aimed to compare nurse satisfaction before and after bedside handover intervention with the SBAR method in the inpatient room. This research is quantitative with a cross-sectional design, the sample of all nurses in the inpatient room is 80 people. The results obtained before the intervention, the highest satisfaction is the need for self-actualization and after the highest satisfaction the need to have. The lowest satisfaction needs before and after the intervention are physiological needs. There is a significant difference between the satisfaction of respondents before and after the intervention. Bedside handover between shift is very useful and gives satisfaction to the nurses, must be carrying out nursing with guidance and supervision and giving rewards to the nurse who practices that when care the patients.